Delivering a gamespeed-focused speed and agility development program in an English Premier League Soccer Academy. - Jeffreys, I.; Huggins, S.; Davies, N. (Strength and Conditioning Journal, 2018)
Speed and agility are highly prized commodities in soccer, but it can be argued that what is crucial is not speed and agility per se, but how these capacities are exploited in the game. Of themselves, speed and agility will be ineffective unless they can be combined with the ability to deploy these capacities to effectively perform the tasks of the game. Optimizing these capacities requires a sophisticated development program that addresses the full gamut of potential constraints to performance. This article outlines how such a development program has been set-up at an english premier league soccer academy.